FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA STAI MUHAMMADIYAH TULUNGAGUNG - Mendah Nur Kumala Jati; Mei Santi; Hasan Sultoni (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
Fostering entrepreneurial interest is one of the alternative options in reducing the unemployment rate in a country. Students as an educated community are expected to be able to be pioneers in growing the soul to do business by becoming young entrepreneurs who have the capacity for good business knowledge, so as to open job opportunities to absorb other workers. Therefore, it takes soul, attitude and mental in order to be able to bear that responsibility. Where the soul, attitude and mental self-entrepreneurship are formed by several intrinsic and extrinsic factors of the individual. The research method used quantitative with the respondents of 50 people is a student who has taken entrepreneurship courses and has been in business. This test uses multiple linear regression analysis that serves to prove the research hypothesis. From the results of the study, it was obtained that all external and internal variables have a positive and significant influence on students' entrepreneurial interests.